Bioaccumulation and translocation of tetrabromobisphenol A and hexabromocyclododecanes in mangrove plants from a national nature reserve of Shenzhen City, South China. (August 2019) - Li, Huawei; Hu, Yongxia; Sun, Yuxin; De Silva, Amila O.; Muir, Derek C.G.; Wang, Weiwei; Xie, Jinli; Xu, Xiangrong; Pei, Nancai; Xiong, Yanmei; Luo, Xiaojun; Mai, Bixian
Abstract: Brominated flame retardants (BFRs) such as tetrabromobisphenol A (TBBPA) and hexabromocyclododecanes (HBCDs) are of ecological concern due to their ubiquitous presence and adverse effects. There is a paucity of data on environmental fate of such compounds in mangrove wetlands, which are unique ecosystems in coastal intertidal areas and act as natural sinks for many pollutants. In this study, mangrove plants and sediments were collected from an urban nature reserve in South China to investigate bioaccumulation and translocation of TBBPA and HBCDs. The mean (range) concentrations of TBBPA and ΣHBCD in roots, stems and leaves were 67 (<MDL-999), 174 (0.73–1105) and 20 (0.59–250) pg/g dry weight (dw), and 329 (15.6–2234), 766 (32.9–3255) and 298 (19.9–1520) pg/g dw, respectively. Tissue-specific accumulations were observed, varying with plant species and compounds. HBCD diastereoisomer patterns were similar for all plant species. γ -HBCD was the major diastereoisomer in roots, while α -HBCD dominated in stems and leaves. The predominance of α -HBCD in aboveground tissues may be ascribed to diastereoisomer-specific translocation, isomerization and/or metabolization in mangrove plants. Preferential enrichment of (−)- α -, (−)- β - and (+)- γ -HBCDs was found in all mangrove plant tissues, suggesting the enantioselectivity for HBCDs in mangrove plants. Translocation factors (log TF, root to stem) of HBCD diastereoisomers and log K ow were negatively correlated ( p = 0.03), indicating passive translocation of HBCDs, driven by water movement during transpiration. Sediment-root bioaccumulation factors and log TFs (stem to leaf) both showed no obvious correlation with log K ow of HBCD diastereoisomers. These results reflected the complex behavior of HBCDs in mangrove plants, which have not been sufficiently captured in laboratory-based studies of plant contaminant accumulation. Graphical abstract: Unlabelled Image Highlights: TBBPA and HBCDs in natural mangrove plants were first reported. TBBPA and HBCDs levels in Futian mangrove plants were relatively low. Diastereo- and enantio-selective behaviors of HBCDs were found in mangrove plants. Translocation of HBCDs from root to stem was negatively correlated with log K ow . Foliar uptake could be an important pathway for SOCs to enter mangrove plants.